Accountability Mechanisms in Faith-Based Organizations: A Case Study of an Islamic Philanthropy Institution in Indonesia - Desti Fitriani; Arika Tri Sugiharti (Politeknik Siber Cerdika Internasional, 2026)
Background: Faith-based NGOs in Indonesia occupy a unique position at the intersection of religious obligation and public governance. While accountability research on NGOs has grown substantially, existing studies predominantly examine secular or general nonprofit contexts, leaving the accountability dynamics of values-based Islamic institutions underexplored. Objective: This study aims to identify the key stakeholders and evaluate the accountability mechanisms within philanthropic institutions. Methods: This study adopts a single case study design focusing on a faith-based organization engaged in Islamic philanthropy in Indonesia. Data were collected through semi-structured interviews, direct observation, and document analysis. The analysis was conducted using a thematic approach, complemented by the constant comparative method to identify patterns and variations in accountability practices. Results: The findings indicate that the organization has implemented five key accountability mechanisms: disclosure and reporting, performance evaluation, participation, self-regulation, and social audit. However, the implementation of these mechanisms remains suboptimal. Future research is recommended to undertake a comparative analysis across multiple NGOs to examine the relationship between accountability mechanisms and the level of public trust in philanthropic institutions in Indonesia. Conclusion: The upward-biased accountability structure identified in this study reflects a broader governance challenge in Indonesian faith-based NGOs, where regulatory and donor compliance pressures systematically crowd out participatory and reflective accountability to beneficiaries.